Interleukin-1 beta modulates the acute release of growth hormone-releasing hormone and somatostatin from rat hypothalamus in vitro, whereas tumor necrosis factor and interleukin-6 have no effect. - Honegger, J; Spagnoli, A; D'Urso, R; Navarra, P; Tsagarakis, S; Besser, G; Grossman, AB (1991)
There is clear evidence for communication between the immune and neuroendocrine systems. However, the effect of cytokines as major immune mediators on the hypothalamic growth peptides, GHRH and somatostatin (SRIH), is not well established. To investigate a possible hypothalamic action of the cytokines interleukin-1 beta (IL-1), interleukin-6, and tumor necrosis factor-alpha, on the release of GHRH and SRIH, we used a previously validated acute rat hypothalamic explant system. IL-1 caused a pronounced dose-dependent stimulation of SRIH in the dose-range 1-100 U/ml (P less than 0.01). GHRH showed a slight, but significant, increase in response to IL-1 tested in the dose-range 10-100 U/ml. Similar studies with mediobasal hypothalamic (GHRH and SRIH) or median eminence (SRIH) fragments produced no change in either GHRH or SRIH release. The effects of IL-1 were antagonized by the cyclo-oxygenase inhibitor, indomethacin (10 micrograms/ml). Stimulation of GHRH and SRIH could not be blocked by the CRH-antagonist alpha-helical CRH (9-41) at 10(-6) M. Interleukin-6, in the dose range 10-100 U/ml, and tumor necrosis factor-alpha, in the dose range 10-10,000 U/ml, had no effect on the acute hypothalamic release of either GHRH or SRIH. It is concluded that IL-1 stimulates the acute hypothalamic release of GHRH and SRIH, and that this effect is mediated by cyclo-oxygenase products. The marked IL-1 stimulation of hypothalamic SRIH release may override the minor increase of GHRH increase, and may thus contribute to disturbances in growth seen in the presence of chronic inflammation.